Reduction in exhaled nitric oxide tracks improved patient inhaler compliance in difficult asthma–a case study. (2nd December 2018) - Hunt, Eoin; Flynn, Deirdre; MacHale, Elaine; Costello, Richard W.; Murphy, Desmond M.
ABSTRACT: Introduction : Exhaled nitric oxide is believed be a useful surrogate for airways inflammation while non-adherence with therapy is known to be associated with worsening of asthma control. Case : We present the case of a 49-year-old female with steroid-dependent asthma and an exacerbation rate of >20/year. She was enrolled in a 3-month-long prospective study using a validated diagnostic inhaler device that provided objective evidence of inhaler compliance. Fractional exhaled nitric oxide (FeNO), peak expiratory flow rates, asthma control questionnaires were measured throughout the study period. Peripheral eosinophil count was obtained prior to the study, during the study, and immediately afterwards. Results : Improvement in compliance at the end of the study led to significant improvements in lung function peak expiratory flow rate (PEFR), and objective scores of asthma. There was an observed improvement in PEFR after 4 weeks, with an associated decrease in FeNO from 92 to 9 ppb that plateaued over the remainder of the study. Her eosinophil count was 0.79 × 10 9 /litre prior to starting in the study, 0.37 × 10 9 /litre after 2 months, and 0.1 × 10 9 /litre at the end of the study. Conclusion : We believe that this is the first case study to objectively prove that improvements in compliance can lead to dramatic reductions in the overall inflammatory airway response and in particular that improvements in patient compliance are mirrored by marked reduction in FeNO levels. These changes occurred in tandem with an observed clinical improvement in our patient.